Luteal phase serum progesterone level as a predictor of vaginal bleeding or adverse pregnancy outcome in patients undergoing assisted reproductive techniques - Kale, Ashish; Kale, Ashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: With advances in assisted reproductive techniques its becoming increasingly important to identify pregnancies having a potential of adverse outcome in the form of per vaginal bleeding or early pregnancy loss. The objective of this study was to find out whether the value of luteal phase progesterone can be used as a marker to predict the possibility of per vaginal bleeding and early pregnancy loss in cases conceived by in vitro fertilization (IVF) and embryo transfer (ET). Methods: A total of 40 women of age less than or equal to 40 years undergoing IVF and ET were included in this study depending upon inclusion criteria. Patients were excluded if they had any factor defined as exclusion criteria. on D14 after embryo transfer B-hCG was done in all the patients. If B-hCG levels were found to be ≥ 100 mIU/ml then serum progesterone levels were also done. B-hCG levels were repeated after 48 hours. Pregnancies were followed up and correlation between suboptimal rise in serum progesterone levels and adverse pregnancy outcome was studied. Results: Mean Beta-hCG and Serum progesterone levels on D14 of embryo transfer were found to be 388.86±34 mIU/ml and 54.24±4.32 ng/ml respectively. A repeat B-hCG and serum progesterone level 48 hours after initial estimation showed mean B-hCG and serum progesterone level to be 598.80±52.12 mIU/ml and 72. 24±5.24 ng/ml respectively. Out of 40 patients 26 patients showed >30% rise in serum progesterone level while 14 patients showed less than 30% rise in serum progesterone level. Conclusions: Suboptimal rise in serum progesterone level (<30%) was associated with increased incidence of adverse pregnancy outcome in women conceived after in vitro fertilization and embryo transfer.